Common errors, successful debugging, and engagement during block-based programming using educational robotics in elementary education - Socratous, Chrysanthos; Ioannou, Andri (My University, 2020)
The study aimed to understand the effect of a structured versus an unstructured Educational Robotics (ER) curriculum on student’s (a) quantity and type of programming errors in block-based programming, (b) ability to find and debug errors, and (c) engagement in the learning process. We worked with a sample of 35 elementary school students in two groups, experiencing one of the teaching approaches: structured versus unstructured ER curriculum. We employed a mixed-method approach based on video and screen recorded data from eight ER lessons, post-experience focus-group interviews, and post-experience questionnaires on students’ engagement and debugging skills. Findings show that there is a list of errors commonly made by students in both groups. Moreover, the unstructured curriculum group was associated with significantly higher amount of errors than the structured curriculum group. Also, a structured curriculum was related to significantly greater efficiency in finding and debugging errors. However, the results revealed that students in the unstructured curriculum outperformed the structured curriculum in terms of their engagement levels.
Keywords: Educational Robotics; Constructivist learning environments